2005
DOI: 10.1007/s00381-005-1231-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome in young adults with spina bifida and hydrocephalus

Abstract: There was a relation between everyday mathematics, reading skills, and quality of life. The consequences of the physical, medical, and cognitive effects of spina bifida extend into young adulthood and have an impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 28 publications
2
81
0
2
Order By: Relevance
“…Many other studies reported a similar association [2,3,11,12,16,28]. Davis et al [9] looked at 158 adolescents and reported 84% of the individuals were shunted.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Many other studies reported a similar association [2,3,11,12,16,28]. Davis et al [9] looked at 158 adolescents and reported 84% of the individuals were shunted.…”
Section: Discussionmentioning
confidence: 72%
“…Parents of the 50 subjects were interviewed in person during the MM clinic using two HRQOL outcome tools: the PedsQL TM Version 4.0 [7,[24][25][26][27] parent version for young children (ages 5-7), children (ages [8][9][10][11][12], and the teen report (ages [13][14][15][16][17][18]; and the PODCI Version 2.0 [10] parent form for children (ages 2-18). Because of concerns about time and length of the instrument, 22% of the parents declined to complete the PODCI questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The presence of a CSF shunt and complications of shunt treatment are associated with compromised cognitive function as well as poorer prospects for survival. Hetherington et al 27 studied 31 adults with myelomeningocele and shunt-treated hydrocephalus who had verbal and performance IQs greater than 70. Patients were categorized according to myelomeningocele level: L-1 and above or L-2 and below.…”
Section: Hydrocephalusmentioning
confidence: 99%